HUBUNGAN TINGKAT PENGETAHUAN DENGAN KEPATUHAN MINUM OBAT DAN LUARAN KLINIS PASIEN HIPERTENSI DI PUSKESMAS SETU 1 KABUPATEN BEKASI TAHUN 2025 - Putri, Intan Auliya; Marselina, Marselina; Dewi, Masita Sari; Adiwisastra, Nuzul Gyanata (Jurnal Buana Farma, 2025)
Hypertension is a non-communicable disease that is a major health problem in Indonesia, especially in industrial areas such as Bekasi Regency. Patient knowledge of hypertension affects adherence to treatment and the success of therapy as measured by clinical outcomes in the form of blood pressure achievement. This study aims to determine the relationship between the level of knowledge with medication adherence and clinical outcomes in hypertensive patients at the Setu 1 Community Health Center in Bekasi Regency. This study used a quantitative design with a cross-sectional approach, involving 91 respondents selected using a purposive sampling technique. The instruments used included the HK-LS questionnaire to assess knowledge, the MMAS-8 for adherence, and medical record data for clinical outcomes. The analysis results showed a significant relationship between the level of knowledge with medication adherence (p = 0.009) and clinical outcomes of blood pressure (p = 0.003). It can be concluded that the higher the patient's level of knowledge, the higher the adherence to treatment and the success of achieving target blood pressure.